Inclusive Education Policy Implementation for Special Needs Children in KB Ar-Ra'uuf Yoeandi, Sidoarjo Regency - Yuanita Ayu Wisudarini; Agus Sukristyanto; Joko Widodo (Cita Konsultindo Research Center, 2024)
This study aims to analyze the implementation of Inclusive Education policy in KB Ar-Ra'uuf Yoeandi. The objectives of the study are to understand the implementation of Permendiknas No 70 Year 2009 on Inclusive Education Article 3 in KB Ar-ra'uuf Yoeandi, to identify the inhibiting and supporting factors in the implementation of the policy, and to find an effective model for the implementation of the policy. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and document analysis. The data is analyzed using the policy implementation model of Elmore, Lipsky, Hjem, and O'Porter. The results of the study show that KB Ar-Ra'uuf Yoeandi has successfully implemented the inclusive education policy using a combination of strategies, such as an inclusive curriculum, RTI and Montessori-based learning, and active participation of all stakeholders. Supporting factors, such as disability-friendly school infrastructure, and inhibiting factors, such as limited human and financial resources, affect the implementation process. The contextualized implementation model is considered the most relevant in understanding the complexity of implementation and the influence of internal and external school factors on its success. This study provides an important contribution to understanding best practices for achieving inclusive education. KB Ar-Ra'uuf Yoeandi is a successful example of creating an inclusive and friendly educational environment for all students, and provides inspiration for other schools to improve inclusivity in the educational environment.